2005
DOI: 10.1007/s11046-003-4790-5
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of Candida albicans by selected essential oils and their major components

Abstract: Many volatile oils are known to possess antifungal properties and are potentially applicable as antimycotic agents. By studying the efficacy of essential oils against different pathogenic mycetes, we have evaluated the in-vitro inhibiting activity of some essential oils and their main constituents against a strain of Candida albicans. Sixteen commercial essential oils and forty-two pure constituents (alcohols, aldehydes, ketons, phenols and hydrocarbons), were tested by using a semisolid agar antifungal suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
129
2
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(148 citation statements)
references
References 10 publications
10
129
2
7
Order By: Relevance
“…Besides cinnamon, other essential oils exhibited high efficacy, as laurel and mint. Both plants have high concentrations of 1,8-cineole, in association with other substances, for instance, menthol in the case of peppermint oil, which has been indicated as an antimicrobial agent [39,40]. Ezzat [38], who investigated the antifungal ability of several essential oils by the DD method, found that Mentha piperita had activity against C. albicans, a similar result obtained in our work.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Besides cinnamon, other essential oils exhibited high efficacy, as laurel and mint. Both plants have high concentrations of 1,8-cineole, in association with other substances, for instance, menthol in the case of peppermint oil, which has been indicated as an antimicrobial agent [39,40]. Ezzat [38], who investigated the antifungal ability of several essential oils by the DD method, found that Mentha piperita had activity against C. albicans, a similar result obtained in our work.…”
Section: Discussionsupporting
confidence: 87%
“…This work evaluated the anti-candidial activity of eight plant essential oils usually presents on mouthwashes and toothpastes, and with their antimicrobial properties recognized [15,[36][37][38][39][40]. Our results showed that the isolates susceptibilities to oils differed among them, except between laurel and mint (P [ 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the Gram-negative bacteria tested were resistant to the essential oil. Other studies of essential oil components reported by Tampieri et al, (17) showed that the monocyclic terpenes, limonene and α-pinene, were not active against C. albicans and cyclic monoterpenic alcohol, 4-terpineol, had low activity. On the other hand aromatic bicyclical β-pinene showed strong inhibitory activity at low concentrations.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, limonene, the major Table 1. component (89.89%) found in the essential oil of Lithraea molleoides (Vell. ), although bereft of antimicrobial activity (17) has anti-carcinogenic activity (2) and can be used in medical dissolution of gallstones (6,10). The results of the analysis of the chemical composition of the essential oil of Lithraea molleoides (Vell.)…”
Section: Discussionmentioning
confidence: 99%